Procession crosses the lanes of Versova Koliwada - Mumbai Archive Project Team (Jio Institute, 2024)
The procession makes its way through the lanes of Versova Koliwada, accompanied by revelry and dancing on the streets. Though organized by the Kolis, people from all communities join the festivities.